2017
DOI: 10.1074/jbc.m117.801704
|View full text |Cite
|
Sign up to set email alerts
|

The stress-regulatory transcription factors Msn2 and Msn4 regulate fatty acid oxidation in budding yeast

Abstract: The transcription factors Msn2 and Msn4 (multicopy suppressor of mutation proteins 2 and 4) bind the stress-response element in gene promoters in the yeast However, the roles of Msn2/4 in primary metabolic pathways such as fatty acid β-oxidation are unclear. Here, analysis revealed that the promoters of most genes involved in the biogenesis, function, and regulation of the peroxisome contain Msn2/4-binding sites. We also found that transcript levels of are increased in glucose-depletion conditions and that dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 48 publications
(52 reference statements)
1
29
0
Order By: Relevance
“…In this regard, considering the fact that Cit2 functions in the glyoxylate cycle, the relevance of peroxisomes in the adaptation of yeast cells to an osmotic environment is reinforced [ 18 ]. The low but significant increase in CIT2 expression under stress in RTG2 -lacking cells can be explained by additional regulatory mechanisms, including the up-regulation of this gene by Msn2/Msn4 under glucose-limiting conditions to support peroxisomal function [ 9 , 24 ] or through interaction with the carbon catabolite repression pathway [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, considering the fact that Cit2 functions in the glyoxylate cycle, the relevance of peroxisomes in the adaptation of yeast cells to an osmotic environment is reinforced [ 18 ]. The low but significant increase in CIT2 expression under stress in RTG2 -lacking cells can be explained by additional regulatory mechanisms, including the up-regulation of this gene by Msn2/Msn4 under glucose-limiting conditions to support peroxisomal function [ 9 , 24 ] or through interaction with the carbon catabolite repression pathway [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a concentration threshold for both of these, where the inactivation of Msn2/4 is reverted. It has been shown that yeast cells lacking Msn2 and Msn4 exhibit prevalent repression of glycolytic genes and a significant delay of acetyl-CoA accumulation and reentry into growth from quiescence as well as impaired expression of genes involved in the fatty acid oxidation and present an increment in triacylglycerol and steryl ester levels [8,9]. As the depletion of these transcription factors seems to affect the metabolic function of the cell, a more targeted intervention to PKA/Msn2/4 system may contribute to the improvement of alcoholic fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…One key downstream effect of Tpk activity is the regulation of the localization of the functionally redundant Msn2 and Msn4 (Msn2/4) stress response transcription factors which are phosphorylated and sequestered in the cytoplasm [43,44]. Upon stress or inhibition of PKA activity, Msn2/Msn4 phosphorylation decreases allowing for translocation into the nucleus where they bind to stress response elements (STREs) and activate transcription of genes related to β oxidation of fatty acids, glycolysis, and stress response [45][46][47]. Interestingly, Msn2/4-dependent transcription is de-repressed in NuA4 mutants [20].…”
Section: Introductionmentioning
confidence: 99%